تقنيات الكتابة الروائية رواية "اختفاء السَّيِّد لا أحد" لأحمد طيباوي نموذجا -  ڨنفود هاجر فقريش خديجة, د / بوديسة بولنوار (université mohamed boudiaf .m'sila, 2023)
Abstract : This study, tagged "Pneumatic writing techniques", is included in the novel "The disappearance of Mr. Nobody" by Ahmed Tibaoui in the framework of studies that seek to reach the world of contemporary Algerian pastoralism by studying a model of Algerian pneumatic "Ahmed Tibaoui" and tagged with: "The disappearance of Mr. Nobody", and the presentation of a preliminary conception of the contents of the narrative and its characteristic narrative structure, which conferred upon it the discretion and distinction, if at the level of experimentation or exceeding the prevailing, by supporting it and vaccinating it from the body of the narrative with graphic and imaginary structures that combined the recollection of its memories with the reality; These structures infuriated the recipient and provoked him to go through a thorough reading, thorough analysis, and attempt to look and reflect on her secrets, mysteries and mines. The importance of this narrative lies in the fact that it constitutes one of the narrative models of the Arab Library and its accountability and analysis, which will alert the reader to a possible path to access the world of criticism, and give recipients mediated analysis and interpretation different possibilities of reading and illuminate its dimensions.
Keywords: Keywords: Narrative writing techniques, Ahmed Tibawy, the disappearance of Mr. Nobody, manifestations and manifestations of narrative structure